The Nitrate-Responsive Protein MdBT2 Regulates Anthocyanin Biosynthesis by Interacting with the MdMYB1 Transcription Factor - Wang, Xiao-Fei (Plant Physiol, 2018)
In addition to scavenging reactive oxygen species, anthocyanins are pigments that give organs their color. In apple (Malus domestica), R2R3-MYB transcription factor MdMYB1 is a master regulator of anthocyanin biosynthesis and fruit coloration. In this study, we found that MdMYB1 was degraded via a ubiquitin-dependent pathway in response to nitrate, an inhibitor of anthocyanin synthesis. Using a yeast two-hybrid (Y2H) approach, we found that the BTB-TAZ protein encoded by the nitrate-responsive gene MdBT2 interacts with MdMYB1. Pull-down and coimmunoprecipitation assays supported this conclusion. In vivo and in vitro experiments revealed that MdBT2 promoted the ubiquitination and degradation of MdMYB1 through a cullin protein MdCUL3-independent pathway. Expression analysis demonstrated that MdBT2 and MdMYB1 were inversely regulated by nitrate and other environmental signals. Furthermore, we used transgenic approaches in apple and Arabidopsis (Arabidopsis thaliana) to characterize the function of MdBT2 in regulating anthocyanin biosynthesis in response to nitrate. Our findings provide insight into a mechanism involving the MdBT2-MdMYB1 pathway that regulates anthocyanin accumulation in apple and possibly in other plant species.